Fertility preservation in patients with uterus didelphys and endometrial carcinoma: a case report - Jiao Yu; Jing Shang; Hongwu Wen; Yang Xu (BMC, 2021)
Abstract Background Endometrial cancer combining uterus didelphys is quite rare clinically which partially explains that there is no discussion about young patients' fertility preservation and follow up of tumor outcome. Case presentation In this article, we report a case of unilateral endometrial carcinoma found in a young patient with uterus didelphys who was treated with high-efficiency progesterone due to unfinished child-bearing. During the follow-up, the affected uterine endometrium was not reversed by progesterone. So, the patient underwent the abdominal surgery with the left uterus and left fallopian tube resection. We performed three consecutive immunohistochemical studies of the contralateral uterine endometrium to verify the safety of preserving the contralateral uterus and its appendages which preserved her fertility. Conclusions Endometrial cancer occurring in patients with uterus didelphys is quite rare in child-bearing age. In this case report, we preserved the patient's contralateral uterus based on patient's strong needs and negative IHC analysis of the preserved side uterine endometrium. However, the tumor and fertility outcome require more follow-up.